Association of both consistency and strength of self-reported clinician recommendation for HPV vaccination and HPV vaccine uptake among 11- to 12-year-old children. Issue 45 (27th October 2017) - Finney Rutten, Lila J.; St. Sauver, Jennifer L.; Beebe, Timothy J.; Wilson, Patrick M.; Jacobson, Debra J.; Fan, Chun; Breitkopf, Carmen Radecki; Vadaparampil, Susan T.; MacLaughlin, Kathy L.; Jacobson, Robert M.
Abstract: Purpose: We tested the hypotheses that consistency and strength of clinician recommendation of the human papillomavirus (HPV) vaccination would be associated with vaccine delivery rates. Methods: From October 2015 through January 2016, we conducted a survey of primary care clinicians (n = 227) in Southeastern Minnesota to evaluate clinician behaviors regarding HPV vaccination. The survey response rate was 41.0% (51 clinical sites). We used the Rochester Epidemiology Project, a clinical data linkage infrastructure, to ascertain clinical site-level HPV vaccination rates. We examined associations of clinician self-reports of both the consistency and strength of their recommendations for HPV vaccination for patients aged 11–12 years (n = 14, 406) with site-level vaccination rates. Results: The majority of clinicians reported consistently (always or usually) recommending the HPV vaccine to females (79.0%) and to males (62.2%); 71.9% of clinicians reported strongly recommending the vaccine to females while 58.6% reported strongly recommending to males. Consistency and strength of recommending the HPV vaccine was significantly higher among those practicing in pediatrics and board certified in pediatrics compared to family medicine. Higher rates of initiation (1 dose) [Incidence Rate Ratio (IRR) = 1.05; 95% CI (1.01–1.09)] and completion (3 doses) [IRR = 1.08; 95% CI (1.02–1.13)] were observed among clinical sites where, on average, clinicians more frequently reported always or usually recommending the vaccine for females compared to sites where, on average, clinicians reported recommending the vaccine less frequently. Similarly, higher rates of initiation [IRR = 1.03; 95% CI (1.00–1.06)] and completion [IRR = 1.04; CI (1.00, 1.08)] were observed among sites where clinicians reported strongly recommending the vaccine to females more frequently compared to sites where, on average, clinicians reported strongly recommending the HPV vaccine less frequently; similar associations were observed for male initiation [IRR = 1.05; CI (1.02, 1.08)] and completion [IRR = 1.05; 95% CI (1.01, 1.09)]. Conclusions: Consistency and strength of HPV vaccination recommendation was associated with higher vaccination rates.